Models of intellectual capital and indicators in the public university - González Millán, José; Rodríguez Díaz, Miryam (Cuadernos de Administración, 2010)
In the context of knowledge management is immersed a highly relevant aspect, not just accounting, but also productive and competitive, which is today called Intellectual Capital (IC). This item has crossed the barrier of finance to become a valuable tool used in business and academic environment of modern organizations. This document recounts, through a theoretical construct and bibliography of the definitions and known models on the subject, through synthesis, compilation and documentary collection, ultimately establishing relevant indicators on the role of public universities Colombian and, thus, by outlining a step in the design of performance indicators in the social role of postgraduate education or higher, as it is called in our society.